Past and future of the connection between project, technology and neocybernetics - Theo Zaffagnini; Otello Palmini (Agathón)
The paper compares design sciences and the philosophy of technology to contribute to the understanding of the concept of innovation in the digital era. Firstly, this work retraces an encounter between these two dimensions that took place in Italy in the late 1960s in order to compare it with some contemporary research perspectives. This operation investigates the evolution of the connection between humans and machines in design, particularly focusing on the systemic approach. Cybernetic thinking and its developments are the links between the two moments (investigated in the text both from a theoretical point of view and through examples). Secondly, it will be shown that a different interpretation of cybernetics can open up the possibility of a new understanding of the relationship between technology and design. A perspective capable of merging a holistic approach and attention to differences and aimed at providing a contribution to the reflection on theoretical paradigms through which technological innovation can be deployed.